Pengaruh Minat Kuliah dan Minat Bekerja Terhadap Perencanaan Karir Pada Siswa Kelas XII SMA Negeri 10 Kota Ternate - Katidja, Siti Sulastri Aprilia; Hi Umar, Suryani (Peneliti.net, 2024)
The research aims to determine whether there is an influence of interest in studying and interest in work on the career planning of class XII students at SMA Negeri 10 Ternate City. This research was conducted on class XII students in the even semester of the 2023/2024 academic year. The type of research used is quantitative research with the research method being a survey method, the survey method is a research method with the research instrument in the form of a questionnaire, where the questionnaire is distributed to class XII students directly, using random sampling techniques.This research obtained the results of the variable interest in studying (X1) tcount < ttable, namely 0.082 < 1.666. This means that there is no influence between interest in studying and career planning, which means that H1 is rejected. Variable interest in work (X₂) tcount > ttable, namely 4.250 > 1.666. This means that there is an influence between work interest and career planning, which means that H2 is accepted. The results of the fcount > ftable test are 12.033 > 3.13. This means that although the variable interest in studying has no effect on career planning, if interest in studying and interest in working together it will improve the career planning of class XII students at SMA Negeri 10 Ternate City, which means H3 is accepted.This research concludes that there is no influence of interest in studying on the career planning of class And there is a relationship between interest in studying and interest in working on students' career planning together, although the variable interest in studying has no effect on students' career planning, but if the increase in interest in studying together with interest in working will increase the career planning of class XII students at SMA Negeri 10 Ternate City.